INCREASING THE EMPATHY OF CHILDREN AGED 5-6 YEARS THROUGH STORYTELLING (ACTION RESEARCH IN TUNAS MANDIRI KINDERGARTEN, BOGOR) - Gisca Hagarayu (Al Hanin, 2021)
AbstrackThis study aims to improve the behavior of children aged 5-6 years empathy in kindergarten Tunas Mandiri Bogor. The subjects were children kindergarten group B1 Tunas Mandiri Bogor aged 5-6 years as many as 9 people. The method used is action research. Data collection using the instrument, observation, interviews, and documentation. The results showed that results of the analysis of quantitative data obtained empathy percentage of 66% in the first cycle and 74.2% in the second cycle. These results indicate conformity with the hypothesis that an increase in acts of pre-study to the first cycle and second cycle exceeds 71%, then the hypothesis is accepted. Results of the qualitative analysis based on field notes, interview notes, and also records the documentation to prove that the activities of storytelling can increase the empathy of children aged 5-6 years. Behavioral aspects of empathy that appears after getting action in the form of storytelling activity that is able to accept the other person's perspective, sensitive to the feelings of others and willing to listen to others. Based on quantitative data and qualitative data obtained by researchers that the activities of storytelling can increase the empathy of children aged 5-6 years in kindergarten Tunas Mandiri Bogor.Â Keywords: Empathy, Activity of Storytelling